The Influence Of Tourist Experience On Interest In Visiting The Jakarta Maritime Museum - Vanessa Audi; Feronika Berutu (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
The Jakarta Maritime Museum, despite its rich historical and cultural significance, receives lower visitor numbers compared to nearby attractions. Understanding the role of tourist experience in shaping interest in visiting such cultural sites is crucial to enhancing their appeal and sustainability. This study employed a quantitative research design using a structured online questionnaire distributed to 100 respondents who had visited or were familiar with the museum. Data were analyzed using SPSS 27, incorporating descriptive statistics, validity and reliability tests, simple regression analysis, and hypothesis testing. The findings revealed a positive and significant influence of tourist experience on visiting interest. The regression coefficient was 0.404, with a t-value of 7.662, surpassing the critical value of 1.984 (p < 0.05). The coefficient of determination (R²) was 0.375, indicating that tourist experience explains 37.5% of the variation in interest to visit the museum. These results highlight the importance of enhancing service quality, emotional engagement, and visitor interaction to improve interest in visiting the Jakarta Maritime Museum. The findings offer practical insights for museum management and contribute to the broader literature on heritage tourism development in emerging economies.